The Concept of Wasatiyyah in Governing the Muslim Community of Singapore - MUHIDIN, IHSAN; MUHAMAD, NASRUL HISYAM NOR; KAMARUDIN, MOHD KHAIRY; DARAWI, ABDUL BASIT SAMAT; NOOR, SULAIMAN SHAKIB MOHD; ABDULLAH, AZWAN (The journal of contemporary issues in business and government, 2021)
Wasatiyyah is the original nature of Islam, therefore Allah calls Muslims as ummatan wasatan. The principle of wasatiyyah is the reason why Islamic sharia can be relevant to be practiced anywhere and at all times, including in secular countries such as Singapore. This article discusses the concept of wasatiyyah implemented by MUIS and related institutions in governing the Muslim community in Singapore. The research method in this article is qualitative with a literature review approach. The collected data was analyzed using the opinion of scholars or experts in the field of sharia law. From the results of this study, the author concludes that in governing the Muslim community of Singapore, MUIS and related institutions have adopted the concept of wasatiyyah.